Conscientiousness and mindfulness in midlife coping: An assessment based on MIDUS II. (22nd November 2015) - Sesker, Amanda A.; Súilleabháin, Páraic Ó; Howard, Siobhán; Hughes, Brian M.
Abstract: Research has demonstrated that conscientious individuals tend to engage in planful problem solving to cope with stressful situations. Likewise, mindful individuals tend to favour approach‐based coping and are less likely to engage in avoidant coping strategies. To examine whether conscientiousness and mindfulness determined agentic coping behaviour, hierarchical linear regressions were conducted using data from 602 participants drawn from the National Survey of Midlife Development in the United States (MIDUS) Study II and MIDUS II Biomarker Project. Personality responses were derived from the five‐factor model inventory, gathered at a single time‐point. Results revealed that conscientiousness predicted problem‐focused coping ( p < 0.001; β = 0.23) and inversely predicted emotion‐focused coping respectively ( p < 0.001; β = −0.14), even after controlling for remaining Big Five and confounding variables. Mindfulness also predicted problem‐focused coping ( p < 0.001; β = 0.21). Neuroticism predicted emotion‐focused coping ( p < 0.001; β = 0.40). These findings suggest that conscientiousness and mindfulness may contribute to coping responses in potentially healthful ways, highlighting new evidence regarding the potential protective role of conscientiousness. Copyright © 2015 John Wiley & Sons, Ltd.